2006
DOI: 10.1159/000089778
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Functional Bowel Disorders: Is There Room for Antibiotics?

Abstract: Small bowel bacterial overgrowth is a syndrome associated with a broad range of predisposing conditions, characterized by the presence of pathological amounts or types of bacteria at the level of the small bowel, clinically evident with a spectrum of symptoms such as diarrhea, flatulence, abdominal pain and bloating. Some of these symptoms are very common complaints in patients suffering from functional bowel disorders (FBDs). Although the pathophysiological mechanisms responsible for FBDs are certainly multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Several broad‐spectrum systemic antibiotics such as fluoroquinolones, metronidazole, tetracycline, amoxicillin‐clavulanic acid, chloramphenicol, etc., have been used to manage SIBO . However, they are usually associated with several and sometimes severe AEs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several broad‐spectrum systemic antibiotics such as fluoroquinolones, metronidazole, tetracycline, amoxicillin‐clavulanic acid, chloramphenicol, etc., have been used to manage SIBO . However, they are usually associated with several and sometimes severe AEs …”
Section: Discussionmentioning
confidence: 99%
“…Several antibiotic regimens proved to be effective over the past 50 years, with treatment success ranging from 27% to 100% . Till the end of 90s, only systemic antimicrobials were used, whose adverse events (AEs) and detrimental effects on gut microbiota are today well known .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 It has also been suggested that prophylactic rifaximin may offer a useful approach for preventing traveller's diarrhea, 41 that rifaximin for 7e10 days once a month may be useful in patients with symptomatic diverticulosis 42 and that it may represent an attractive alternative to prevent or limit NSAID-associated intestinal damage. 43 With respect to the results of our study showing rapid rifampin resistance after rifaximin intake, these broad and prophylactic indications may pose a problem in-hospital settings, especially in centres with prosthetic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Different drugs (and different dosages) with a success rate ranging from 30% to 100% have been employed. 4 The systematic review and meta-analysis of Shah et al 5 represent a welcome and timely effort to provide clinicians with an evidence-based treatment of SIBO. The authors found that antibiotics are more effective than placebo (OR: 2.55; 95% CI: 1.29-5.04) in patients with symptoms attributable to SIBO.…”
mentioning
confidence: 99%